PREDICTION OF PHOTOSYNTHETIC RESPONSES BY MATHEMATICAL MODEL: गणितीय प्रतिरूप द्वारा मुख्य पादप कार्यिकी अनुक्रियाओं का पूर्वांकलन - Verma, Krishan; Verma, Chedilal; Singh, Munna; Singh, Yash Pal; T., Damodaran; Singh, A.K.; Mishr, Vinay (International Journal of Research -GRANTHAALAYAH, 2020)
English: Plant photosynthetic responses such as photosynthesis, transpiration rate and stomatal conductance are interrelated. There is a definite tendency for variability between photosynthetic responses and leaf positions at different branches. The variability is in the form of diurnal variations relative to the leaf positions of photosynthesis, transpiration and stomatal conductance on the same branch of Jatropha curcas plants. This research paper presented shows that the correlation between plant photosynthetic responses through mathematical modeling. Through the proposed model, the characteristic of plant responses constants for jatropha plants were calculated and the different deviation from their observed value was calculated by calculating the different plant photosynthetic parameters. In the comparative study, the average deviation of the photosynthetic responses ranged from 1.69 - 13.21. This model can be easily used in calculating plant photosynthetic responses according to their leaf positions on the branches of other plants. Hindi: पादप कार्यिकी अनुक्रियायें यथा प्रकाश संश्लेषण, उत्स्वेदन एवं रंघ्रीय चालकता परस्पर सह संबंधित हैं। शाखाओं पर विभिन्न स्थितियों पर अवस्थित पर्णों के पादप कार्यिकी अनुक्रियाओं एवं पर्ण स्थिति के बीच परिवर्तनीयता की एक निश्चित प्रवृत्ति होती है। जट्रोफा की सरल शाखा पर स्थित विभिन्न पत्तियों के प्रकाश संश्लेषण, उत्स्वेदन दर एवं रंघ्री चालकता की पर्ण स्थिति के सापेक्ष परिवर्तनीयता एक घण्टाकृति के रूप में होती हैं। प्रस्तुत शोध पत्र में पादप कार्यिकी अनुक्रियाओं के परस्पर सह संबंध को गणितीय सूत्र के माध्यम से दर्शाया गया है। प्रस्तावित प्रतिदर्श के द्वारा जट्रोफा के लिये अभिलाक्षणिक पादप कार्यिकी युगल अनुक्रिया स्थिरांकों की गणना की गयी एवं उनसे विभिन्न पादप कार्यिकी अनुक्रियाओं की गणना करके उनके प्रेक्षित मान से प्रतिशत विचलन की गणना की गयी। तुलनात्मक अध्ययन में कलित पादप कार्यिकी अनुक्रियाओं का औसत विचलन 1.69 से 13.21% के बीच रहा। इस प्रतिदर्श का प्रयोग अन्यान्य पौधों के शाखाओं पर अवस्थित पत्तियों की उनकी स्थिति के अनुरूप पादप कार्यिकी अनुक्रियाओं की गणना में सहजता पूर्वक किया जा सकता है।